An intermediate wheatgrass model for APSIM next generation - Innes, P. J.; Newell, M. T.; Pembleton, K. G.; Hayes, R. C.; Radanielson, A. M. (Elsevier, 2025)
Perennial cereals, for dual purpose grain and forage production, are being considered as an alternative to annual cereals in many grazing and cropping enterprises. Field experiments in NSW Australia and elsewhere have identified candidate species, such as intermediate wheatgrass and mountain rye, which produce both grain and biomass over a two-to-three year period. Existing experimental data pertaining to the phenology and yields of perennial cereals are mostly from higher latitude temperate regions of North America. There are sparse data to inform the likely growth and yields of perennial cereals in warmer latitudes. This study aimed to address this gap using the APSIM Next Generation crop simulation program. A model for one of the candidate perennial cereals, intermediate wheatgrass, was constructed within APSIM. The model was then used to predict the likely phenology, biomass, and grain yields of intermediate wheatgrass in diverse environments under varying management regimes. The model was parameterised using phenology and yield datasets from Australia and North America. Validation of the model, using a different selection of datasets, indicated a strong phenology prediction accuracy (r²=0.96, RMSE=7.94 (Zadoks scale)). Prediction accuracies for above ground biomass and grain yield were acceptable (r²=0.75, RMSE=2372 kg/ha and r²=0.80, RMSE=148 kg/ha respectively). The model responded appropriately to irrigation and fertiliser inputs. Further simulations, using a transect of locations from sub-tropical Queensland to temperate Tasmania, indicated that successful grain production, given the current vernalisation requirements of intermediate wheatgrass, is likely restricted to temperate zones of the current cereal cropping regions in Australia. The Intermediate Wheatgrass model is the only comprehensive perennial grains model available at present. It will be a valuable tool for both plant breeders and farm planners when developing new cultivars and/or defining suitable geographical regions for new perennial grains crops, such as intermediate wheatgrass.